The potential of STEM-based curriculum in realizing 21st-century learning: Bibliometric analysis - Wahyudin Wahyudin; Muhammad Rafi Valliansyah; Cindy Sri Meidina Adeliani; Muhammad Bahrul Ulum (Inovasi Kurikulum, 2024)
Education, in general, cannot be separated from various existing problems. One of these problems is a gap between graduate education and industry needs. This causes multidisciplinary learning, such as STEM, to be carried out. Extracting information related to research in the STEM curriculum field as an effort to realize 21st-century learning is important. This research aims to analyze the scope of STEM-based curriculum research in realizing 21st-century learning using a bibliometric review. Data collection was carried out through the Scopus database with the keywords ("STEM competency" AND "21st learning skills") OR (stem AND "21st learning skills") OR (stem AND curriculum AND student) from 2020 to 2025. This research discusses general information analysis, annual research production, most relevant sources, local impact sources, local impact authors, most relevant affiliations, country of correspondence author, country of production of scientific articles, most cited countries, most cited documents, tree map and related thematic map with previously defined keywords. This research found that the project-based learning model (PjBL) is suitable for implementation in STEM-based curricula to realize 21st-century learning. Some potential research keywords are students, curriculum, engineering education, engineering, motivation, and curriculum development.   Abstrak Pendidikan secara umum tidak lepas dari berbagai permasalahan yang ada. Salah satu masalah tersebut adalah terdapat kesenjangan antara lulusan pendidikan dan kebutuhan industri. Hal ini menyebabkan pembelajaran multidisiplin ilmu seperti STEM perlu dilakukan. Penggalian informasi terkait penelitian dalam bidang kurikulum STEM sebagai upaya mewujudkan pembelajaran abad ke-21 menjadi penting. Penelitian ini bertujuan untuk menganalisis ruang lingkup penelitian kurikulum berbasis STEM dalam mewujudkan pembelajaran abad ke-21 dengan menggunakan tinjauan bibliometrik. Pengumpulan data dilakukan melalui database scopus dengan kata kunci ("STEM competency" AND "21st learning skills") OR (stem AND "21st learning skills") OR (stem AND curriculum AND student) dari tahun 2020 sampai 2025. Penelitian ini membahas analisis informasi umum, produksi riset tahunan, sumber paling relevan, local impact sumber, local impact penulis, afiliasi paling relevan, negara korespondensi penulis, negara produksi artikel ilmiah, negara yang paling banyak disitasi, dokumen yang paling banyak disitasi, tree map dan thematic map terkait dengan kata kunci yang telah ditetapkan sebelumnya. Penelitian ini menemukan bahwa model pembelajaran berbasis proyek (PjBL) cocok diimplementasikan dalam kurikulum berbasis STEM dalam mewujudkan pembelajaran abad ke-21. Beberapa kata kunci penelitian yang potensial berupa students, curricula, engineering education, engineering, motivation, dan curriculum development. Kata Kunci: analisis bibliometrik; kurikulum berbasis STEM; pembelajaran abad ke-21; pemrograman R; pendidikan